The production model based on Lean Manufacturing and TPM to increase the level of efficiency in a company in the manufacturing sector - Guerrero Telles, Sofia Valentina (2025)
The present research focused on measuring the level of efficiency based on the implementation of Lean Manufacturing and TPM. Relevant data for the research were collected before and after the implementation to identify problems and design solutions based on Smed, Standardized Work and TPM. First, a root cause analysis was performed with the problem tree tool, where problems such as long set up stoppages, breakdowns, lack of maintenance, lack of training of the production team, among others, were identified. Therefore, a solution proposal was implemented based on the methodologies, which improved the efficiency level from 50% to 79.3%. Based on this, the application of the SMED tool focused on decreasing the setup time, the mold change lasted about 7.06 hours and decreased 5.97 hours. In the case of standard work, operational failures were reduced from 15% to 6%. On the other hand, the implementation of TPM increased the efficiency of the machinery together with preventive maintenance training for the equipment, which increased from 37.56% to 51.31%. Finally, these findings highlight the importance of implementing tools such as Lean Manufacturing and TPM in the manufacturing sector to increase the level of efficiency in the organization.